Antidermatophytic Activites Of Azadirachta Indica : An In Vitro And In Vivo Study - Ranganathan S; Menon Thangam; Balajee Arun Mozhi S; Raja Mahendra S (Wolters Kluwer Medknow Publications, 1996)
The leaf and seed extracts of Azadirachta indicia were tested for antifungl activity against dermatophytes by in vitro and vivo tests. The minimum inhibitory concentration (MIC) of neem seed extract was found to be lower than that neem leaf when tested against different species of Trichophyton and Epidermophyton floccosum. Experimental lesion in guinea pigs healed better after treatment with neem seed extract when compared to untreated control animals.